Sinterização de cerâmicas multiferróicas nanoestruturadas de Pb(Fe1/2Nb1/2)O3 e Pb(Fe2/3W1/3)O3 via Spark Plasma Sintering SPS - Nascimento, William Junior do (2013)
Considering the search for miniaturization of electronic devices, the development of new methods and techniques for the production and characterization of nanostructured materials is fundamental, beyond understanding of the effect of grain size on the properties of materials in nanoscale. Therefore, it was proposed in this work the obtaining of nanostructured multiferroic materials, in bulk, with high density and microstructural control, with grains ranging from micrometer to nanometer scale. To achieve this goal, was developed a methodology for obtaining the powder of lead iron niobate, Pb(Fe1/2Nb1/2)O3 (PFN) and lead iron tungstate, Pb(Fe2/3W1/3)O3 (PFW), with average particle size around 150 nm, contamination-free, minimal agglomeration and with highly reproductive results using the micro-milling technique. Regarding consolidation materials, conventional sintering requires higher temperatures and long holding times for a satisfactory densification, resulting in a grain growth higher than the desired. Through the fast sintering technique, only high heating rates are not sufficient to ensure a satisfactory densification and also inhibit the growth of grains. The obtain nanostructured dense samples with average grain size of approximately 200 nm was only possible using spark plasma sintering technique (SPS), which allows sintering at temperatures corresponding to the intermediate sintering stage, inhibiting the grain growth. PFN and PFW samples obtained through the SPS technique showed high conductivity at room temperature due the extreme reduction suffers in the system plus the use of high current densities during sintering, being necessary the samples oxidation. Through the dielectric characterization, the decrease in grain size of micrometer to nanometer scale results in lower permittivity values in phase transition temperature, besides a peak broadening. Moreover, the SPS technique added to the oxidation process makes it possible to obtain PFW samples with high dielectric values (in order of 104) at room temperature, a motivation results with regard to the application.